(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
The objectives of this study were to identify, from verbal reports, controlling variables of studying and working behaviors in a group of young college students and to determine the existence of verbal operant classes on the working behavior. The sample was constituted by 107 young college students from a private university in the city of São Paulo (40 workers and 67 non-workers), ages between 19 and 24 years. Five groups have been held to access the verbal reports under the control of verbal discriminative stimuli. The data analysis has been executed with the help of the software ALCESTE 4.5. The results indicate the emission of different verbal tacts among the young workers that the working behavior is maintained under the positive reinforcer “money” and by self-rules control. A similarity between young workers and young non-workers indicated an aversive discriminative function of the concurrency between working and studying behaviors.